Caroba-tree and Brazilian peppertree germinative response to salinity stress and application of salicylic acid - Braga, André Caturelli [UNESP]; Santos, Marina Moreira [UNESP]; da Silveira, Mariana Martins [UNESP]; Campos, Thiago Souza [UNESP]; de Souza, Antonio Maricélio Borges; Pivetta, Kathia Fernandes Lopes [UNESP] (FapUNIFESP (SciELO), 2024)
Abiotic stresses, such as salinity, interfere with the growth and development of plants and can reduce, delay, or even inhibit the germination of the seeds. The knowledge about ornamental plants tolerance to those factors and the search for alternatives that reduce those effects, as is the use of salicylic acid, indicate paths to better development of the plants in environments affected by those stresses. This work aimed to evaluate the germination of Caroba-tree seeds and Brazilian peppertree seeds in different saline concentrations of sodium chloride (NaCl), using salicylic acid, as a possible saline stress attenuator. The experimental design utilized was completely randomized, with treatments arranged in factorial scheme 4 x 2 being four saline concentrations (0, 30, 60, and 90 mM of NaCl) combined with the absence (immersion in distilled water) or presence of salicylic acid (immersion in a solution containing salicylic acid at 1.0 mM). It was concluded that Caroba-tree showed moderate tolerance to salinity promoted by NaCl during seed germination. The average germination percentage was 83.91%. However, the seeds germinated at slower paces with the increasing saline solutions. The application of salicylic acid at the concentration of 1.0 mM did not influence the germination percentage of seeds subjected to saline solutions, regardless of the concentration. However, the seeds germinated faster in the absence of salicylic acid. Brazilian peppertree was not tolerant to salinity promoted by NaCl, with an average germination percentage of 47% and 40%, respectively, for the absence and presence of salicylic acid.
Resposta germinativa de sementes de jacarandá-caroba e aroeira-vermelha ao estresse salino e aplicação de ácido salicílico
Keywords: abiotic stress; estresse abiótico; Jacaranda brasiliana; mitigation; mitigação; salinidade; salinity; Schinus terebinthifolius